Selective exposures in orthopaedic surgery the pelvis - Gorczyca, John T.; American Academy of Orthopaedic Surgeons (Rosemont, Ill. : American Academy of Orthopaedic Surgeons, 2005)
Enables the participant to recognize the architecture of the pelvis, this includes the osseous ligamentous, neurologic, vascular, and muscular anatomy; to evaluate how to safely expose pelvic structures using various approaches; to apply techniques for placement of retractors, clamps and surgical implants; to locate, visualize, isolate, tag, retract, and protect the neurovascular structures encountered with each exposure; to understand the indications for each surgical exposure; to anticipate and avoid the operative pitfalls present in each exposure; and to comprehend the principles and details of pelvic wound closure.
Anatomy of the pelvis -- Anterior exposures -- Posterior Exposures -- Lateral exposure
DVD
Keywords: Pelvis -- surgery; Orthopedic Procedures -- methods